La optimización de los procesos financieros y tributación de las unidades estratégicas del sistema integrado de recreación, bienestar y alojamientos militares de la armada Nacional de Colombia. - Rumbo Camelo, Edwin Alexander (Universidad Antonio Nariño, 2021)
This research work to apply for the title of Master in Financial and Tax Management considers the Optimization of Financial Processes and Taxation of the Strategic Units of the Integrated System of Recreation, Welfare and Military Accommodations of the Colombian National Army as a general objective. For which the solution to three specific objectives will be developed, which are to characterize the operation of the Recreation Centers of the National Army and its Strategic Business Units, determine the administrative and financial procedures with which the Army Recreation Centers operate. National and its Strategic Business Units and finally establish the tax management of the Recreation Centers of the National Navy and its Strategic Business Units. This will be achieved by investigating the information, financial and tax statements and indicators of the Recreation Centers, Official Chambers and NCOs under a mixed approach is a collection and analysis procedure that links quantitative and qualitative data in the same study through research with the generalization of results that are collected with numerical data of the objects, or participating units, that demonstrate the viability or otherwise of the results obtained in the sample to a selected population.